Epimedium Aqueous Extract Ameliorates Cerebral Ischemia/Reperfusion Injury through Inhibiting ROS/NLRP3-Mediated Pyroptosis - Xiaoyu Wu; Jiajia Wei; Yang Yi; Guotao Shu; Zhixu He; Qihai Gong; Jianmei Gao (Antioxidants, 2023)
Cerebral ischemia/reperfusion causes exacerbated neuronal damage involving excessive neuroinflammation and oxidative stress. ROS is considered a signal molecule to activate NLRP3; thus, the ROS/NLRP3/pyroptosis axis plays a vital role in the pathogenesis of cerebral ischemia/reperfusion injury (CIRI). Therefore, targeting the inhibition of the ROS/NLRP3/pyroptosis axis may be a promising therapeutic tactic for CIRI. Epimedium (EP) contains many active ingredients (ICA, ICS II, and ICT), which have a wide range of pharmacological activities. However, whether EP can protect against CIRI remains unknown. Thus, in this study, we designed to investigate the effect and possible underlying mechanism of EP on CIRI. The results showed that treatment with EP dramatically mitigated brain damage in rats following CIRI, which was achieved by suppressing mitochondrial oxidative stress and neuroinflammation. Furthermore, we identified the ROS/NLRP3/pyroptosis axis as a vital process and NLRP3 as a vital target in EP-mediated protection. Most interestingly, the main compounds of EP directly bonded with NLRP3, as reflected by molecular docking, which indicated that NLRP3 might be a promising therapeutic target for EP-elicited cerebral protection. In conclusion, our findings illustrate that ICS II protects against neuron loss and neuroinflammation after CIRI by inhibiting ROS/NLRP3-mediated pyroptosis.